Sendemails: An automated email package with multiple applications - Luca Fumarco; S. Michael Gaddis; Francesco Sarracino; Iain Snoddy (Masaryk University, Faculty of Economics and Administration, 2023)
Correspondence audits are a popular method to examine discrimination in a causal framework. However, they often require sending hundreds or thousands of emails to subjects. The sendemails package allows users to automatically send emails with Stata through PowerShell, which is open-source and cross-platform. Researchers can use this package to perform several email tasks, such as contacting students or colleagues with standardized messages. Additionally, researchers can perform more complex tasks that entail sending randomized messages with multiple attachments from multiple accounts, tasks that are often necessary to conduct correspondence audit tests. This paper introduces the command and illustrates multiple examples of its application.
Keywords: C8; 330; sendemails; PowerShell; email